Digital Financial Inclusion, Transaction Costs, and MSME Productivity: Micro Evidence from Indonesia - Saragih, Iwan (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2025)
This study examines the impact of digital financial inclusion ontransaction costs and productivity of MSMEs in Indonesia usingmicro-panel data (≈1,400 MSMEs; multiple waves) and a quasiexperimentalapproach. The identification strategy combinesdifference-in-differences (DiD) with fixed effects, event studies toexamine parallel trends, and instrumental variables (IV) basedon supply-side variations (agent density and signal quality) toaddress endogeneity of adoption. Key variables include adoptionand depth of use of digital financial services (payments,bookkeeping, sales channels), transaction cost indices(monetary, time, and coordination costs), and productivityindicators (output per worker, operating margin). Results showthat digital adoption increases output per worker by ≈ Rp2.1million/year (p<0.001) and operating margin by ≈ +2.3percentage points; IV estimates confirm causality with a slightlylarger impact (≈ Rp2.6 million/worker/year). Incorporating atransaction cost index into the model reduces the adoptioncoefficient, suggesting mediation through reduced transactionfriction—specifically savings in reconciliation time and monetarycosts (MDR/cash-out). Nonlinear analysis identifies a benefitthreshold of around –0.5 SD on the cost index: cost reductionsbelow the threshold trigger a productivity surge, while above thethreshold the effect weakens. The impact is stronger in micro-SMEs, the food and beverage sector, players with high digitaldepth, and urban areas. The findings are consistent acrossrobustness tests (PSW/entropy balancing, pre-adoption placebo,and alternative outcome/index definitions). Practically, inclusionpolicies need to shift from simply encouraging adoption toreducing the most “binding” cost components per segment andencouraging digitalization depth (payments–bookkeeping–saleschannels), accompanied by infrastructure expansion and trainingin disadvantaged areas.